Effects of Zinc Ions Released From Ti-NW-Zn Surface on Osteogenesis and Angiogenesis In Vitro and in an In Vivo Zebrafish Model - Zhu, Wen-Qing; Li, Kang; Su, Shan; Chen, Wei; Liu, Yao; Qiu, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Zinc-modified titanium materials have been widely applied in oral implants. Among them, our previous studies have also successfully prepared a novel acid-etched micro-structured titanium surface modified with zinc-containing nanowires (Ti-NW-Zn) and proved its excellent biocompatibilities. It is well known that the functional regulation between angiogenesis and osteogenesis is of great importance for bone remodeling around implants. However, there are few reports concerning the biological safeties of zinc ions released from materials and the appropriate concentration of released zinc ions which was more conducive to angiogenesis and bone regeneration. In this study, we investigated the effects of zinc ions released from Ti-NW-Zn surfaces on angiogenesis and osteogenesis via zebrafish model, and revealed the relationship between angiogenesis and osteogenesis via HUVECs and MC3T3-E1s in vitro. We found that the zinc ions released from Ti-NW-Zn surfaces, lower than median lethal concentrations (LCs) of zebrafish, were biologically safe and promote the osteogenesis and angiogenesis in vivo. Moreover, the proper concentration of zinc ions could induce the proliferation of HUVECs and osteogenic differentiation. The positive effects of the appropriate concentration of zinc ions on osteoblast behaviors might be regulated by activating the MAPK/ERK signaling pathway. These aspects may provide new sights into the mechanisms underlying zinc-modified titanium surfaces between osteogenesis and angiogenesis, to lay the foundation for further improve the materials, meanwhile, promote the applications in dentistry.